(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated the marketing of frozen fish in Kaduna metropolis, Kaduna state. Ten (10) markets were purposively selected due to high concentration of frozen fish marketers and the volume of trading activities; Primary data were generated through the use of structured questionnaire administered to hundred (100) randomly selected retailers and fifteen (15) purposively selected wholesalers. The data were analyzed using descriptive statistic, budgeting technique, net marketing and rate of return on capital invested. The result show that majority 80 percent and 53 of the retailers and wholesalers were female, Majority (70prcent) of the retailers had primary education but most of the wholesaler’s attained tertiary education. The frozen fish marketing channels identified in the area are made up of zero and multi stage channels. Furthermore, the cost and return analysis revealed that the wholesalers realized about N121, 000.00 naira while the retailers got N56, 000.00 naira per month while return to per capital invested (RPCI) was 11 kobo and 22 kobo per Naira invested for the wholesalers and the retailers respectively. This implies that the enterprise is profitable. Transportation difficulties and marketing charges ranked were major constraints confronting frozen fish marketers. It is recommended that provision of good roads network and formidable integrated marketing system will further improve the profitability of the enterprise in the study area.